LABOR MARKET TRANSFORMATION IN UZBEKISTAN: CHALLENGES IN EMPLOYMENT POLICY AND THE IMPACT OF DIGITAL ECONOMY TRANSITION - Karshiboyev , Shuhrat; Zulfakarova , Liliya (Scientific practical conference, 2026)
This study examines the transformation of Uzbekistan's labor market between 2018 and 2023, with a focus on the effectiveness of active employment policy (AEP) programs and the influence of digital economy development on employment outcomes. Employing a panel regression model across 14 regions over six years (N = 84), the research finds that a one-percentage-point increase in AEP expenditure relative to GDP reduces the unemployment rate by 0.41 percentage points (β = −0.412, p < 0.001). The digitalization index independently reduces unemployment by 0.29 percentage points (β = −0.289, p < 0.001). A field survey (n = 420, Jizzakh region) reveals that 71.4% of workers are willing to acquire digital skills, while 54.7% fear job displacement from automation. The study identifies regional disparity, skills mismatch, and the unregulated gig economy as key structural barriers to full employment. Six evidence-based policy recommendations are proposed, including a Digital Skills Passport system, a revised National Qualifications Framework, and legal protections for platform workers.